Botany, traditional usages, phytochemistry, pharmaceutical analysis, and pharmacology of Eleutherococcus nodiflorus (Dunn) S.Y.Hu: A systematic review. (24th April 2023) - Li, Xiaojun; Tang, Siqi; Luo, Jiao; Zhang, Xiaodan; Yook, Changsoo; Huang, Hao; Liu, Xiangqian
Abstract: Ethnopharmacological relevance: Eleutherococcus nodiflorus (Dunn) S.Y.Hu (Araliaceae), also called Eleutherococcus gracilistylus, Acanthopanax gracilistylus, and Xi-zhu-wu-jia (Wujiapi or Nan Wujiapi) in Chinese, is a widely used traditional Chinese herb with the effects of dispelling pathogenic wind and eliminating dampness, nourishing liver and kidney, diuresis and detumescence, promoting blood circulation for removing blood stasis, and strengthening the bones and tendons according to the theory of Traditional Chinese Medicine (TCM). It has been used as medicine for the treatment of paralysis, arthritis, rheumatism, lameness, body asthenia, fatigue, edema, beriberi, and liver diseases. Meanwhile, E. nodiflorus (EN, thereafter) has ginseng-like activities known as "ginseng-like herb". Aims of the review: This review aims to present comprehensive information for the research progress of EN, including taxonomic position, botany, traditional usages, phytochemistry, pharmaceutical analysis, pharmacology and toxicology. Among them, phytochemical and pharmacological studies are mainly focused. Materials and methods: Relevant literature was acquired from scientific databases including Web of Science, PubMed, Google Scholar, Baidu Scholar, SciFinder and Chinese national knowledge infrastructure (CNKI). Monographs and Chinese pharmacopeia were also utilized as references. Results: In the past decade, a great number of phytochemical and pharmaceutical analyses, as well as pharmacological studies on EN have been carried out. Several kinds of chemical compositions have been reported, including essential oil, sesquiterpenes, diterpenes, triterpenes, phenylpropanoids, lignans, caffeoyl quinic acids, flavonoids, steroids, fatty acids, ceramides as well as other compounds, among which, diterpenes and triterpenes were considered to be the most active components. The fingerprint chromatography, qualitative and quantitative analysis were used for the methods of quality control of EN. Considerable pharmacological experiments in vitro and in vivo have demonstrated that EN possessed hypoglycemic, anti-inflammatory, anticancer, anti-ageing, anti-fatigue, immunomodulatory, hepatoprotective, antioxidant, anti-AChE, anti-BuChE, anti-hyaluronidase, and antiobesity activities. Conclusions: As an important TCM, a large number of investigations have proved that EN and terpenoids isolated from EN have markedly therapeutic efficacy on diabetes, inflammation, and cancer disorders. These research findings provide modern scientific evidence for the traditional uses of EN. Moreover, more novel and active secondary metabolites from EN, as well as the in vivo and clinical in-depth tests are required in the future. Graphical abstract: Image 1 Highlights: Eleutherococcus nodiflorus (Dunn) S.Y.Hu (EN) is a widely used traditional Chinese herb based on the theory of Traditional Chinese Medicine. This review aims to present comprehensive information for the research progress of EN, including botany, traditional usages, phytochemistry, pharmaceutical analysis, and pharmacology. The phytochemical and pharmacological studies are mainly focused. The patents included EN are also reviewed.